RISIKO PENGETAHUAN, AKTIVITAS DAN FISIOLOGI TERHADAP KEJADIAN OBESITAS REMAJA - Nuradan Hasta Santoso; Kun Aristiati Susiloretni; Ria Ambarwati (Poltekkes Kemenkes Semarang, 2020)
Background : Prevalence of obesity on 7th and 8th grade students of 40th Junior Highschool Semarang were 8,6%, while the prevalence of obesity in Indonesian adolescents were 2,5%. Obesity was caused by knowledge factor, physiology, activity, socioeconomic, psychology, and food and beverage factor.Subject : To analyze the great risk of knowledge factor include knowledge and attitude variables, activity factor include physical activity, sleep duration, time of watching television, and exercise habits variables, and physiology factor include gender and age variables on the incident of adolescent obesity.Method : An observasional research with case control design with ratio 1:1. There were 35 cases dan 35 control sample. Data collection were included gender, age, knowledge, attitude, physical activity, sleep duration, time of watching television, and exercise habits. Data was analyzed with chi square test and logistic regression with confidence interval 95%.Result : Logistic regression test showed that students were 14-15 years (OR 0.06 95% CI 0.008-0.557), students’ knowledge were 80% (OR 25.67 95% CI 3.57-184.60), students sleep 7 hour/day (OR 30.22 95% CI 2.47-369.26), and students excersise 3 times/week and 30 minutes (OR 13.55, 95% CI 1.145-160.476).Conclusion :There was a significant association between age, knowledge, sleep duration, and exercise habits with incidence of obesity. Further research is to examine risk factors of adolescent obesity with another variable and a larger sample is highly recomended.